Effect of MHD and Porosity on exact solutions and flow of a hybrid casson-nanofluid - Zulkhibri, Ismail; Mohd Zuki, Salleh; Sidra, Aman; Syazwani, Mohd Zokri; Khan, Ilyas (Akademi Baru, 2018)
In this work, a novel hybrid nanofluid model with advanced thermophysical properties is considered for Casson fluid. The exact solutions are evaluated for noninteger derivative equations via Laplace technique. The unsteady flow, MHD, radiation and porous medium are considered. For the hybrid concept, alumina and copper nanoparticles are used in this research investigation. The problem is modeled using Caputo definition of non-integer derivatives. The influence of concerned parameters is depicted physically and graphically on the heat, concentration and flow of the hybrid nanofluid. The effect of volume fraction of both the nanoparticles on flow of hybrid nanofluids is observed. It is found that velocity increases with increasing values of Gr, b , and k, whereas M decreases.